The role of energetic factors in the evolution of the breeding biology of the short-tailed shearwater (Puffinus tenuirostris, Temminck) - Kate Fitzherbert. (2020)
This thesis was scanned from the print manuscript for digital preservation and is copyright the author. Researchers can access this thesis by asking their local university, institution or public library to make a request on their behalf. Monash staff and postgraduate students can use the link in the References field.